Science and Technology for Batik Craftsmen Society for Improving Economy of the Community in Surabaya Ex Prostitution Localization - Indah Werdiningsih; . Purbandini; Ira Puspitasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The community development presents the creation of catalog to display products online that can help market widely as an effort to improve economy of the community in the area of exs-red district Bangunsari, Surabaya. Partners are an organization engaged in the development of affected communities in the area of Bangunsari localization. The partners are Omah Batik Tulis Khas Surabaya Sari Ratu and Rumah Batik Canting Risma Ratu. E-catalog application had three proceses, i.e. customer registration process, master data processing process, and ordering process. E-catalog application had through five stages are: 1) Identifies data needs performed by interview; 2) Designing the database, created using a Conceptual Data Model (CDM) that produces 8 entities and Physical Data Model (PDM) that generates 8 tables next design the i nput and output form; 3) Implements the system using a web-based programming language; 4) Testing system with black box method, testing sistem include all transactions on each user; and 5) Evaluation of system was done by using questionnaire to find accuracy of aplication. Questionnaires were distributed to 2 partners. Questionnaire was filled by chairman and two members for each partner. Number of questionnaire was 6 questionnaires. The evaluation results show that accuracy of e-catalog application that had been built was user friendly for 73.61%. It is clear that e-catalog aplication that had been built had good category for user friendly.